2009
DOI: 10.3402/gha.v2i0.1881
|View full text |Cite
|
Sign up to set email alerts
|

Providing free maternal health care: ten lessons from an evaluation of the national delivery exemption policy in Ghana

Abstract: BackgroundThere is a growing movement, globally and in the Africa region, to reduce financial barriers to health care generally, but with particular emphasis on high priority services and vulnerable groups.ObjectiveThis article reports on the experience of implementing a national policy to exempt women from paying for delivery care in public, mission and private health facilities in Ghana.DesignUsing data from a complex evaluation which was carried out in 2005–2006, lessons are drawn which can inform other cou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
98
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 94 publications
(102 citation statements)
references
References 6 publications
4
98
0
Order By: Relevance
“…Existing empirical evidence indicates that a less noisy environment and modern recreational facilities help patients recover in a timely manner. 12,25 The significant contribution of culture to patient's satisfaction at university hospitals is very interesting. It reflects the idea that patients' satisfaction with healthcare delivery is influenced by language, religion, and ethnic background.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Existing empirical evidence indicates that a less noisy environment and modern recreational facilities help patients recover in a timely manner. 12,25 The significant contribution of culture to patient's satisfaction at university hospitals is very interesting. It reflects the idea that patients' satisfaction with healthcare delivery is influenced by language, religion, and ethnic background.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have confirmed that patients share the view that healthcare service that is culturally sensitive to their healthcare needs ensures satisfaction and promotes quality healthcare delivery. 10,12 Moreover, prioritizing healthcare based on patients' needs is relevant to ensuring healthcare delivery. Previous studies on patient satisfaction have revealed that priority care is fundamental to the assessment of service quality at hospitals.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, generating political will for safe motherhood in Indonesia (Shiffman, 2003), the state of political priority for safe motherhood in Nigeria (Shiffman and Okonofua, 2007), the emergence of political priority for safe motherhood in Honduras (Shiffman et al, 2004), and actors practise of power in a South African community health programme (Lehmann and Gilson, 2013). Most empirical research on maternal health in Ghana and other LMICs (Travis et al, 2004, Borghi et al, 2006, Adam et al, 2005, Gupta et al, 2011, Asamoah et al, 2011, Phillips et al, December 2006, Witter et al, 2009) focused more on implementation challenges such as scarcity of resources, shortage of skilled health personal, inadequate quality of care, and recommendations of potential policies that should improve maternal health, and less on how the implemented policies came onto the national agenda and formulated. Studying how those implemented policies were put on the agenda and formulated may give additional insights into why the policies face several implementation challenges.…”
Section: Research Problem Objective and Questionsmentioning
confidence: 99%
“…Over the years, policy makers at national level have formulated a wide range of public policies and programmes to increase financial and geographical access to maternal care; space child birth; provide essential obstetric care; expand midwifery coverage; and make equipment and health facilities available and many more to improve maternal health outcomes and reduce maternal deaths in Ghana (Government of Ghana, 2006, Ministry of Health, 2011b, Ministry of Health, 2007, Ministry of Health et al, 2011, Witter et al, 2009, Ofosu-Amaah, 1981.…”
Section: Introductionmentioning
confidence: 99%